High Intensity Interval Training: Enhancing Health Outcomes for Individuals with Coronary Artery Disease - Ruslan, Ruslan; Rusli , Rusli; Sarifin G; Andi Sri Dewi Anggraeni. M (Kinestetik : Jurnal Ilmiah Pendidikan Jasmani, 2024)
Coronary artery disease (CAD) contributed to morbidity and mortality significantly in the world that is characterized by accumulation of atherosclerotic plaque within the arterial walls. Individuals with CAD often experience reduced functional capacity, lower quality of life (QoL), and elevated rates of depression This study aims to explore high-interval intensity training (HIIT) benefits in coronary artery disease patients. This study is a review literature that uses the existing database on PubMed and Google Scholar with the year 2019 to 2024 which specifically discusses High interval intensity training in coronary artery patients. The results of the study revealed that the benefits of high interval intensity training have an impact such as increasing physical capacity, namely VO2 and cardiovascular health and have a good impact on mental health. High interval intensity training is beneficial for people with coronary artery disease even though the first hour of exercise takes time for body adjustment. The implementation of high interval intensity training needs to involve professionals.